Efficacy of warfarin reversal in orthopedic trauma surgery patients. - Tharmarajah, P; Pusey, J; Keeling, D; Willett, K (2007)
OBJECTIVES: We determine the efficacy of active reversal of warfarin anticoagulation with intravenous vitamin K compared to withholding warfarin in patients requiring urgent orthopedic trauma surgery. DESIGN: This was a prospective cohort with immediate prehypothesis consecutive retrospective comparative case series conducted at a level 1 university hospital trauma unit. PATIENTS: Forty-eight consecutive patients between 1998 and 2004 in a study composed of a prospective cohort were compared with a retrospective consecutive case series of warfarinized orthopedic trauma patients requiring urgent surgery. The prospective arm directly followed the historic case series from which the hypothesis was generated. INTERVENTION: Vitamin K administration. MAIN OUTCOME MEASURES: Primary outcome was time to surgery. Secondary outcomes were problems with active reversal, length of time for warfarin stabilization after surgery, and complications. RESULTS: The mean time to surgery in warfarinized patients not given vitamin K was 111.9 hours; in the intervention group, it was 67.4 hours, giving a mean difference of 44.5 hours (P = 0.01). Vitamin K reduced the international normalized ratio (INR) to less than 2.0 in 74% of patients within 24 hours. There were no complications of vitamin K administration. A dose of vitamin K costs approximately 1/1000 of a hospital bed day cost. A loading dose of warfarin on the second postoperative day took approximately 1 day longer to reach an INR of greater than 2.0 in the intervention patients than in those who had not been given vitamin K. CONCLUSIONS: Warfarin reversal with vitamin K was successful and facilitated earlier surgery in all patients; the first dose was effective in approximately three quarters of patients. It is cost-effective, with no side effects caused in this study.